(8a-14)(2a-6)=

Simple and best practice solution for (8a-14)(2a-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8a-14)(2a-6)= equation:

Simplifying
(8a + -14)(2a + -6) = 0
Reorder the terms:
(-14 + 8a)(2a + -6) = 0
Reorder the terms:
(-14 + 8a)(-6 + 2a) = 0
Multiply (-14 + 8a) * (-6 + 2a)
(-14(-6 + 2a) + 8a * (-6 + 2a)) = 0
((-6 * -14 + 2a * -14) + 8a * (-6 + 2a)) = 0
((84 + -28a) + 8a * (-6 + 2a)) = 0
(84 + -28a + (-6 * 8a + 2a * 8a)) = 0
(84 + -28a + (-48a + 16a2)) = 0
Combine like terms: -28a + -48a = -76a
(84 + -76a + 16a2) = 0
Solving
84 + -76a + 16a2 = 0
Solving for variable 'a'.
Factor out the Greatest Common Factor (GCF), '4'.
4(21 + -19a + 4a2) = 0
Factor a trinomial.
4((7 + -4a)(3 + -1a)) = 0
Ignore the factor 4.
Subproblem 1Set the factor '(7 + -4a)' equal to zero and attempt to solve:
Simplifying
7 + -4a = 0
Solving
7 + -4a = 0
Move all terms containing a to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + -4a = 0 + -7
Combine like terms: 7 + -7 = 0
0 + -4a = 0 + -7
-4a = 0 + -7
Combine like terms: 0 + -7 = -7
-4a = -7
Divide each side by '-4'.
a = 1.75
Simplifying
a = 1.75
Subproblem 2Set the factor '(3 + -1a)' equal to zero and attempt to solve:
Simplifying
3 + -1a = 0
Solving
3 + -1a = 0
Move all terms containing a to the left, all other terms to the right.
Add '-3' to each side of the equation.
3 + -3 + -1a = 0 + -3
Combine like terms: 3 + -3 = 0
0 + -1a = 0 + -3
-1a = 0 + -3
Combine like terms: 0 + -3 = -3
-1a = -3
Divide each side by '-1'.
a = 3
Simplifying
a = 3Solutiona = {1.75, 3}`